Determinants of milk production in FADN dairy farms in the regions of the European Union with predominance of intensive production in 2011 = Determinanty produkcji mleka w gospodarstwach mlecznych FADN w regionach Unii Europejskiej z przewagą intensywnej produkcji w 2011 roku - Guth, Marta (Zielona Góra: Faculty of Economics and Management Press)
The main aim of the considerations was to determine the factors determining the variability of milk production in selected macroregions of the European Union. The regions were selected on the basis of the analysis of the diversity of dairy farms FADN in the regions of the European Union, which was determined by the agglomeration cluster analysis using Ward method.
Keywords: produkcja mleka; regiony Unii Europejskiej; analiza skupień; analiza czynnikowa; determinanty produkcji; milk production; EU regions; cluster analysis; factor analysis; production determinants